BASIC PROPERTIES OF I-ADIC ALGEBRA (Sciences & Technology. A, exactes sciences, 2001)
In this paper we study the basic properties of the I-adic algebras (spectrum, radius of regularity, group of inversible elements, entire functions, etc.).